Clinical procedures for safer patient care - Doyle, Glynda Rees.; BC Open Textbook Project; BCcampus; British Columbia Institute of Technology (BCcampus, BC Open Textbook Project, 2015)
This open educational resource (OER) was developed to ensure best practice and quality care based on the latest evidence, and to address inconsistencies in how clinical health care skills are taught and practised in the clinical setting. The checklist approach, used in this textbook, aims to provide standardized processes for clinical skills and to help nursing schools and clinical practice partners keep procedural practice current. Each skill/procedure is covered in a chapter that has learning objectives, a brief overview of the relevant theory, checklists of steps for procedures with the rationale behind each step of the process, and a summary of key takeaways. Key terms are set in bold throughout the book and laid out again in a Glossary in the appendix. All 88 checklists are also summarized, and hyperlinked to the original checklist, in the appendix."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright 2015, BCIT"--Web version home page http://opentextbc.ca/clinicalskills/.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Patient care -- Safety measures -- Textbooks; Patient care -- methods; Electronic books